2013
DOI: 10.5539/esr.v2n2p135
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Study of the Influence of Mineral Salts on Swelling (KCl, MgCl2)

Abstract: Swelling and shrinkage of expansive soils occur mainly due to a change in the moisture regime and pose serious problems to foundations causing damage to structures founded on them. However, construction on this type of soil requires a good companion for the recognition of identification, characterization of their swelling potential and Treatment processing.In this work we are interested by two aspects:1) The first is on the tests recommended for the identification of diferants expansive soils in the region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The application of the NaCl solutions caused the consolidation and collapse of the sand-clay mixture; as a result of the compression, its hydraulic conductivity was reduced. This result is in agreement with the findings of Belabaci [31] stating that the addition of chlorides increases the mechanical strength and the bearing capacity of clays. Reddy et al [32] see NaCl as a "good stabilizer", since it helps in suppressing the expansion of plastic clay when applying a minimum effort; moreover, it can increase the hydraulic conductivity of liners, although not for all types of clay.…”
Section: Discussionsupporting
confidence: 93%
“…The application of the NaCl solutions caused the consolidation and collapse of the sand-clay mixture; as a result of the compression, its hydraulic conductivity was reduced. This result is in agreement with the findings of Belabaci [31] stating that the addition of chlorides increases the mechanical strength and the bearing capacity of clays. Reddy et al [32] see NaCl as a "good stabilizer", since it helps in suppressing the expansion of plastic clay when applying a minimum effort; moreover, it can increase the hydraulic conductivity of liners, although not for all types of clay.…”
Section: Discussionsupporting
confidence: 93%
“…The amount of lime required to achieve significant improvement varies from 5% to 10% according to the US Army Corps of Engineers, 1994 [7]. Other research studies [8][9][10][11][12][13][14][15][16] reported that the addition of CaCl 2 can increase the initial and long-term strength of constructed roadbed materials and improve their durability due to cation exchange and flocculation of soil particles.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed great reduction in swelling and significant increasing in strength properties of these soils. Belabbaci et al [14] studied the effect of potassium chloride (KCl) and magnesium chloride (MgCl 2 ) solution on increasing the mechanical strength and bearing capacity of clay and it was found that addition of salts increased strength and reduced swelling and soil absorption capacity.…”
Section: Introductionmentioning
confidence: 99%